The Economics of Credence Goods: On the Role of Liability, Verifiability, Reputation and Competition - Uwe Dulleck; Rudolf Kerschbamer; Matthias Sutter (University of Innsbruck, Department of Public Finance, 2009)
Credence goods markets are characterized by asymmetric information between sellers and consumers that may give rise to inefficiencies, such as under- and overtreatment or market break-down. We study in a large experiment with 936 participants the determinants for efficiency in credence goods markets. While theory predicts that either liability or verifiability yields efficiency, we find that liability has a crucial, but verifiability only a minor effect. Allowing sellers to build up reputation has little influence, as predicted. Seller competition drives down prices and yields maximal trade, but does not lead to higher efficiency as long as liability is violated.
Keywords: C72; C91; D40; D82; 330; Credence goods; Experiment; Liability; Verifiability; Reputation; Competition; Vertrauensgüter; Haftung; Wettbewerb; Asymmetrische Information; Marktmechanismus; Test; Theorie